Microbiome in Colorectal Cancer: How to Get from Meta-omics to Mechanism?. Issue 5 (May 2020) - Ternes, Dominik; Karta, Jessica; Tsenkova, Mina; Wilmes, Paul; Haan, Serge; Letellier, Elisabeth
Abstract : Mounting evidence from metagenomic analyses suggests that a state of pathological microbial imbalance or dysbiosis is prevalent in the gut of patients with colorectal cancer. Several bacterial taxa have been identified of which representative isolate cultures interact with human cancer cells in vitro and trigger disease pathways in animal models. However, how the complex interrelationships in dysbiotic communities may be involved in cancer pathogenesis remains a crucial question. Here, we provide a survey of current knowledge of the gut microbiome in colorectal cancer. Moving beyond observational studies, we outline new experimental approaches for gaining ecosystem-level mechanistic understanding of the gut microbiome's role in cancer pathogenesis. Highlights: A pathological imbalance of the gut microbiome (dysbiosis) is present in colorectal cancer (CRC) patients. Bacteria may affect CRC directly or indirectly, by secreting metabolites, by invading tissues, and by modulating the host immune response. The underlying pro-oncogenic mechanisms of many CRC-associated bacteria remain undescribed. Fusobacterium, Peptostreptococcus, Porphyromonas, Prevotella, Parvimonas, Bacteroides, and Gemella are among the most prominent CRC-associated bacteria. Many in vitro and in vivo models are currently used for studying the microbiome in CRC, such as gut-on-chip models, 3D intestinal organoids, and gnotobiotic mouse models, each offering its own advantage. The microbial metabolism plays an important role in CRC. Computational modeling is a promising approach for studying genotype-to-metabolic-phenotype relations or microbe–microbe and host–microbe metabolic interactions.